Genetic control of earliness in cowpea (Vigna unguiculata (L) Walp). Issue 7 (July 2022) - Owusu, Emmanuel Yaw; Kusi, Francis; Kena, Alexander Wireko; Akromah, Richard; Attamah, Patrick; Awuku, Frederick Justice; Mensah, Gloria; Lamini, Salim; Zakaria, Mukhtaru
Abstract: Global climate change is expected to further intensify the already harsh conditions in the dry savannah ecological zones of sub-Saharan Africa, posing serious threats to food and income security of millions of smallholder farmers. Breeding cowpea for improved earliness could help minimize this risk, by ensuring that the crops complete their lifecycle before the cessation of rainfall. In this study, we crossed two sets of cowpea lines showing contrasting phenotypes for earliness in terms of days to 50% flowering (DFF). One set of the lines comprised three extra-early parents (viz.: Sanzi-Nya, Tobonaa and CB27, 30–35 DFF), and the other set consisted of three early-to-medium maturity lines (viz.: Kirkhouse-Benga, Wang-Kae and Padi-Tuya, 42–45 DFF). The derived crosses and their parents were evaluated for key earliness-related traits at Nyankpala and Manga sites of CSIR-Savanna Agricultural Research Institute (SARI), Ghana. To unravel the genetic control of measured traits, we compared the appropriateness of Chi-square goodness of fit tests using classical Mendelian ratios, and frequency distribution (histogram)-related statistics such as skewness and kurtosis. The Chi-square test suggested a single dominant gene mode of inheritance for earliness, whereas the quantitative methods implicated duplicate epistasis and complementary epistatic gene actions. Our results show that coercing segregating lines to fit into classical Mendelian ratios to determine the genetic control of earliness could be misleading, due to its subjectivity. Thus, the genetic control of earliness in cowpea is governed by complementary and duplicate epistasis. The most applicable breeding approach for traits influenced by duplicate epitasis is selection of desirable recombinants from segregating populations developed from bi-parental crosses. Complementary epitasis, as found in the Wang-Kae × CB27 cross, could be exploited in developing improved extra-early lines through backcrossing. Heritability and genetic advance estimates were high for days to first flower appearance (DFFA) and days to 95 % pod maturity (DNPM) in the Padi-Tuya × CB27 and Kirkhouse-Benga x CB27 crosses, indicating that breeding for extra-earliness is feasible. CB27 could be a good donor for introgression of earliness into medium to late maturing improved cowpea varieties, because crosses developed from it had high heritability and genetic advance estimates. Abstract : Duplicate gene epistasis, Complementary gene epistasis, Genetic advance, Heritability, Kurtosis, Skewness, Chi-square test.